A Development and Comparison Study of PVDF Membranes Enriched by Metal-Organic Frameworks - Pisarenko, Tatiana; Papež, Nikola; Al-Anber, Mohammed A; Dallaev, Rashid; Částková, Klára; Ţălu, Ştefan (Polymers, 2025)
This study is concerned with the research and development of nanofibrous hybrid materials functioning as membranes composed of polyvinylidene fluoride (PVDF) polymer and enriched with metal-organic frameworks (MOFs) as dopants for the adsorption and detection of gases, dyes, and heavy metals in wastewater. Several types of nanofiber composites are fabricated by electrostatic spinning. The prepared samples and their chemical, optical, and material properties are analyzed. Subsequently, the preliminary investigation of dye removal is conducted. Accordingly, the design and investigation of these nanofibrous structures may contribute to addressing critical environmental and technological challenges.
Keywords: polyvinylidene fluoride; metal-organic frameworks; dye adsorption; nanofibers; photoluminescence; methylene blue; contact angle; electrospinning; membranes